THE IMPORTANCE OF THE NURSING PROCESS FOR THE PREVENTION AND TREATMENT OF PRESSURE INJURY IN AN INTENSIVE CARE UNIT - Alves, Felipe Silvério; Sousa, Mariana Lobo Mendonça de; Júnior , Ademir Nunes Ribeiro; Moraes, Thiago de Sousa; Boeira, Elisângela Rodrigues (CIPEEX, 2025)
The Nursing Process (NP) is a dynamic tool that seeks to systematize and organize nursing care across various practice scenarios. Thus, the general objective of this research was to evaluate the nursing team’s knowledge about the nursing process as a tool for the prevention and treatment of pressure injury in the Intensive Care Unit. A cross-sectional, descriptive, exploratory study method was used, directed at the nursing team. A field survey was conducted, approaching technicians and nurses working in an intensive care unit in their work environment who agreed to participate in the study. A total of 83 (100.0%) nursing professionals from two hospitals in Goiás participated, comprising 68 (82.0%) technicians and 15 (18.0%) nurses. The majority were women, 66 (81.5%). A high adherence to the Nursing Process was observed, with 68 (81.9%) using it regularly, and 79 (95.2%) believing in its effectiveness. Despite this, only 40 (48.2%) used all stages of the NP. The study highlighted the importance of continuous training and the integration between teaching and practice to improve the application of the NP, aiming to ensure quality and safety in patient care, especially in the prevention and treatment of pressure injuries. The nursing teams in the Intensive Care Units consider the Nursing Process an important tool to support decisions and multidisciplinary activities. However, complete adherence to all stages of the NP is limited. Most professionals know the signs of pressure injury, but the lack of complete knowledge about the NP hinders the effective implementation of preventive and therapeutic care. The study emphasizes the need to promote the NP as an essential and legally supported tool, exclusive to the nurse, to ensure safe care in Intensive Care Units, highlighting the importance of continuous in-service education.